Omsorg för dagen och fostran för en framtid: Irakiska mödrars strategier för att skapa tillhörighet i Sverige (Sociologisk Forskning, 2017)
Caring in the present and fostering for the future: Iraqi mothers’ reconstruction of belonging during resettlement in SwedenThe present study explores Iraqi women’s mothering strategies for protecting, nurturing, and training their child, as well as how they use different approaches to (re)construct feelings of belonging during the process of resettlement. It is qualitative in design and based on individual interviews as well as focus groups discussions with a total of 27 women. Narrative method has inspired the analysis. The results show a child-centred motherhood with everyday practices aimed at creating a sense of safety and belonging for the child. Belonging to the family is central. The child’s societal and future belonging is connected to educational achievement, with prospects of employment and upward mobility. Accordingly, the mothers apply strategies aimed at promoting such a life trajectory. However, aspirations for belonging in the future can sometimes conflict with belonging at the present. In addition, striving to create belonging for the child can be in conflict with the parents’ sense of belonging.
Keywords: mothering; immigrant motherhood; forced migration; resettlement; belonging